2014
DOI: 10.1007/s00284-014-0522-y
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Escherichia albertii Strain, DM104, Induces Protective Immunity to Shigella dysenteriae in Guinea Pig Eye Model

Abstract: The environmental Escherichia albertii strain DM104, which cross-reacts serologically with Shigella dysenteriae was assessed for pathogenic properties, immunogenicity, and protective efficacy in different animal models to evaluate it as a vaccine candidate against S. dysenteriae, which causes the severe disease, shigellosis. The DM104 isolate was found to be non-invasive and did not produce any entero- or cyto-toxins. The strain also showed negative results in the mouse lethal activity assay. The non-pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In another study, the immunogenicity and protective efficacy of a S. flexneri 2a vaccine candidate were compared with a live-attenuated Shigella vaccine strain following intranasal or ocular immunization of guinea pigs [17]. Similarly, this study, along with our previous study [12] carried out with S. dysenteriae type 4 vaccine strain DM104, clearly showed the protective efficacy of a vaccine in the guinea pig model. The high protection in guinea pig models induced by the DM104 strain along with its non-pathogenic properties strongly suggests that the Shigella-cross-reacting DM104 strain may be used as a promising live vaccine candidate against shigellosis.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In another study, the immunogenicity and protective efficacy of a S. flexneri 2a vaccine candidate were compared with a live-attenuated Shigella vaccine strain following intranasal or ocular immunization of guinea pigs [17]. Similarly, this study, along with our previous study [12] carried out with S. dysenteriae type 4 vaccine strain DM104, clearly showed the protective efficacy of a vaccine in the guinea pig model. The high protection in guinea pig models induced by the DM104 strain along with its non-pathogenic properties strongly suggests that the Shigella-cross-reacting DM104 strain may be used as a promising live vaccine candidate against shigellosis.…”
Section: Discussionmentioning
confidence: 59%
“…The guinea pigs were conjunctively inoculated [18] with live S. dysenteriae type 4 (20 μl each, ∼5 × 10 8 CFU/ml, corresponding to five times of the infective dose 50). All these animals were observed daily for 5 days and scored for the development of disease or protection [12,17].…”
Section: Challenge Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…One of these strains, DM104 was phylogenetically identified as Escherichia albertii and showed a similar lipopolysaccharide (LPS) gel banding profile to that of S. dysenteriae type 4 8 . The DM104 isolate was found to be non-invasive, did not produce any entero-or cytotoxins, and showed negative results in the mouse lethal activity assay 9 . As an ocularly administered vaccine in the guinea pig eye model against S. dysenteriae type 4 challenge, the non-pathogenic DM104 strain gave, a high protective efficacy and also induced a high titer of serum IgG against S. dysenteriae type 4 whole cell lysate (WCL) and LPS.…”
Section: Introductionmentioning
confidence: 98%
“…One of these strains, DM104 was phylogenetically identified as E. albertii and showed a similar lipopolysaccharide (LPS) gel banding profile to that of S. dysenteriae type 4 7 . Recently, it was also demonstrated that the DM104 isolate was non-invasive, did not produce any entero-or cytotoxins, and showed negative results in the mouse lethal activity assay 8 . The non-pathogenic DM104 strain gave, however, a high protective efficacy as an ocularly administered vaccine in the guinea pig eye model against S. dysenteriae type 4 challenge.…”
Section: Introductionmentioning
confidence: 99%